Tax Avoidance and Intra-Family Transfers - Katarina Nordblom; Henry Ohlsson (Uppsala University, Department of Economics, 2005)
To what extent do people avoid taxes on intra-family transfers (bequests and gifts), and how would integration (unification) of the different transfers taxes affect tax avoidance? These issues are important for families and their welfare, as well as for governments and their possibilities of raising revenue from transfer taxes. In this paper we study the effects of transfer taxes on altruistic parents transfers to their children. Using a theoretical model we find that altruistic parents do not necessarily tax minimize. However, in some cases when they do, there is an infinitely large excess burden of a transfer tax. We also find that integration of transfer taxes reduces tax avoidance. All tax avoidance is eliminated with complete integration.
urn:nbn:se:uu:diva-79356
Keywords: D10; D64; D91; 330; tax avoidance; bequests; inheritances; inter vivos gifts; altruism; Steuervermeidung; Kinder; Erbe; Geschenk; Altruismus; Familienbesteuerung; Theorie; Eltern